Assessment of the quality of life comparison between open and endovascular aortic arch surgery: a pilot study - Eric Thiam Aik Lim; Hannah S. Kim; Andrew McCombie; Andrew D. P. Laing; Adib Khanafer (Journal of Cardiothoracic Surgery)
Abstract Background Advancement in endovascular endografts have paved the way to the possibility of performing endovascular aortic arch repair in recent years. This has started to supersede the need for open aortic arch surgery. There remains a paucity of data looking into the quality of life comparison between open aortic arch surgery and endovascular aortic arch repair. Method A retrospective, observational pilot study was performed on patients who underwent endovascular inner branched aortic arch repair and open aortic arch surgery. Patients completed the RAND SF-36 questionnaire at the 6 week follow-up post-surgery. Mean score across all eight subscales were compared to the New Zealand population norm based on the New Zealand Health Survey as cited in the SoFIE-Health study. Results A total of 12 patients were included in this study over a 3 year period. We demonstrated that endovascular aortic arch repair is associated with a better quality of life compared to open aortic arch surgery across all eight subscales. Pain scores were found to be higher than the population normal in the endovascular aortic arch repair group while the open aortic arch surgery group had a score lower than the population norm (P < 0.01). Conclusion There appears to be a trend towards better quality of life following endovascular aortic arch repair compared to open aortic arch repair.